Pemodelan Indeks Kualitas Lingkungan Hidup di Indonesia dengan Spline Truncated dan MARS - Fitri, Marfa Audilla; Suliyanto, Suliyanto; Mardianto, M Fariz Fadillah; Ana, Elly (Universitas Nahdlatul Ulama Sunan Giri, 2025)
Background: Indonesia, endowed with abundant natural resources, faces substantial challenges in maintaining environmental quality amid rapid urbanization and economic growth. The 2022 Environmental Performance Index ranked Indonesia 164th out of 180 countries with a score of 28.2. Regionally, Indonesia ranked 22nd among 25 Asia-Pacific countries. The Environmental Quality Index (EQI), crucial for achieving the Sustainable Development Goals (SDGs), was recorded at 72.42 in 2022, classified as